KELAYAKAN SEDIAAN BODY SCRUB OATMEAL DAN DAUN PEGAGAN UNTUK PERAWATAN KULIT KERING - Nelva, Hadisty; Linda Rosalina (Universitas Negeri Jakarta, 2023)
Dry skin often makes women less confident because the skin looks dull and scaly. One type of cosmetic that can be used for skin care is a body scrub. Body scrub is a cosmetic preparation used to maintain the skin. Oatmeal and gotu kola leaves are natural ingredients containing antioxidants that can protect the skin from the dangers of free radicals, which cause dry skin conditions to worsen. Therefore, the purpose of this study is to determine the feasibility of body scrub oatmeal and gotu kola leaves, as reviewed from the level of Vitamin A and flavonoids (laboratory tests), organoleptic tests (texture, aroma, adhesiveness), and hedonic tests (panelists' preferences). This study uses a quantitative research method with an experimental approach. Data collection techniques used are observation methods, documentation, and observation sheets. The study's results from the vitamin A content test are 6.3720%, and the flavonoid content is 0.0094% in 100g of the tested sample. These components moisturize the skin and act as antioxidants, protecting the skin from the dangers of free radicals. Organoleptic tests and hedonic tests show that the body scrub has a rough texture, strong aroma, strong adhesive power, and is liked by the panelists. Thus, the oatmeal and peganum leaf body scrub is suitable for use on dry skin.